2011
DOI: 10.1007/s12177-011-9070-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related adduct formation and retinopathy

Abstract: The pathogenesis of diabetic retinopathy is complex, reflecting the array of systemic and tissue-specific metabolic abnormalities. A range of pathogenic pathways are directly linked to hyperglycaemia and dyslipidaemia, and the retina appears to be exquisitely sensitive to damage. Establishing the biochemical and molecular basis for this pathology remains an important research focus. This review concentrates on the formation of a range of protein adducts that form after exposure to modifying intermediates known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 90 publications
(93 reference statements)
0
12
0
Order By: Relevance
“…The potential clinical application of RAGE blockade include the decreased progression of diabetic retinopathy as upregulation of RAGE leads to pro-inflammatory responses by retinal Müller glia cells [ 83 ]. AGEs play an important role in the progression of diabetic retinopathy, and leads to dysfunction and death of various retinal cells [ 84 ]. The multiple components of the AGE-RAGE axis including signal transduction, formation of ligands, and the end-point effectors can be promising targets for treatments of diabetic retinopathy [ 85 ].…”
Section: Ages and Diabetic Complicationsmentioning
confidence: 99%
“…The potential clinical application of RAGE blockade include the decreased progression of diabetic retinopathy as upregulation of RAGE leads to pro-inflammatory responses by retinal Müller glia cells [ 83 ]. AGEs play an important role in the progression of diabetic retinopathy, and leads to dysfunction and death of various retinal cells [ 84 ]. The multiple components of the AGE-RAGE axis including signal transduction, formation of ligands, and the end-point effectors can be promising targets for treatments of diabetic retinopathy [ 85 ].…”
Section: Ages and Diabetic Complicationsmentioning
confidence: 99%
“…It has been shown that AGEs, by altering the surface charge of the protein, lead to conformational changes and consequently reduces the transparency of the lens of the eye [ 38 ]. AGEs also play an important role in the progression of diabetic retinopathy leading to dysfunction or death of retinal cells [ 39 ]. Recent reports indicate that detoxification of methylglyoxal reduces the accumulation of AGEs, which in turn can prevent the pathological changes in the retina and vessels [ 40 ].…”
Section: Glycationmentioning
confidence: 99%
“…During diabetes, hyperglycaemia is a chronic insult to circulating immune cells and vascular endothelial cells. Furthermore, various intermediate metabolic products such as advanced glycation end-products (AGEs) and advanced lipoxidation end-products (ALE) also constitute insults to tissue cells [68]. Vascular endothelial damage is a main pathology in DR and microaneurysms, a characteristic feature of DR, is believed to be the consequence of endothelial and pericyte cell death [1].…”
Section: Introductionmentioning
confidence: 99%